131I SPECT/CT provides prognostic information in patients with differentiated thyroid cancer - Heinrich, Marieke; Blickle, Elias; Hartrampf, Philipp E.; Hasenauer, Natalie; Kosmala, Aleksander; Kerscher, Alexander; Schlegel, Nicolas; Verburg, Frederik A.; Buck, Andreas K.; Michalski, Kerstin (European Journal of Nuclear Medicine and Molecular Imaging, 2025)
Purpose: The aim of this study is to investigate the impact of lymph node metastases (LNM) detected on cervical 131I single photon emission computed tomography/computed tomography (SPECT/CT) after the first radioiodine therapy (RAI) on complete response (CR) and progression-free survival (PFS) in patients with differentiated thyroid cancer (DTC). Methods: This retrospective study included 942 DTC patients who underwent cervical 131I SPECT/CT after their first RAI. LNM were categorized based on CT (enlarged ≥ 1 cm, small < 1 cm) and 131I uptake. CR and PFS were analysed using Kaplan–Meier curves and Cox regression. Results: Patients with no LNM had a shorter median time to CR (9.4 months) than those with LNM (44 months, HR 2.2; p < 0.01) and a lower risk of progression (median PFS not reached, HR 0.46; p < 0.01). Among patients with LNM, those with enlarged 131I negative LNM had the longest time to CR (24 months, HR 0.36; p < 0.01). Patients with small LNM had a PFS similar to patients without LNM (median PFS not reached, HR 1.22; p = 0.54). Reoperation after first RAI (13.5 months) led to earlier CR than second RAI (median not reached) in patients with enlarged LNM. For small LNM, second RAI was associated with longer PFS than reoperation (38.4 months vs. not reached, HR 4.0; p = 0.02). Conclusion: Patients without LNM on post-therapy 131I SPECT/CT have better chances for early CR and longer PFS. Patients with LNM benefit from early reoperations but treatment strategies should be tailored based on LNM characteristics.
CRIS-Team Scopus Importer:2025-12-15
Keywords: Complete response; Lymph node metastases; Progression-free survival; Radioiodine therapy; Reoperation